Avaliação da memória similar à episódica a partir de uma perspectiva de interação social em ratos wistar - Malheiros, Maria Augustta Sobral de França (2022)
The recall of past events, called episodic memory, is directly related to autobiographical events and considered to be a human singularity, according to (Tulving, 2002). Studies have demonstrated an episodic-like memory in some animals based on behavioral criteria, such as events (“what”) that occurred at a certain place (“where”) and at a certain time ("when"). To be considered an episodic-like memory, these behavioral aspects must be recalled in an integrated and associative way. While the social context is known to influence cognitive and behavioral capacities in different species, few studies have investigated the episodic-like memory. Most studies have been directed towards understanding the neural processes of human or animal behavior evaluated individually, not in a social context. In this study, we tested the processes of encoding and recalling episodic-like memory in a social context by applying an episodic-like memory task. Animals were divided into four groups, namely: control group, in which the animals performed the task individually; experimental dyad sample group, in which the animals performed only the sampling sessions of the task in dyad; experimental dyad test group, in which the animals performed only the test session of the dyad task; and the experimental dyad group, in which the animals performed all sessions of the dyad task. The animals failed to integrate the three episodic criteria in the test session of the task. However, performing the task in pairs seems to be important for rats to access the time and space index of the episodic-like memory after an interval of 24 h. No difference was found in the expression of c-Fos in the dorsal hippocampus and CA1, CA2, CA3, and GD subregions. Our findings open the way for investigations that explore experimental designs of behaviors analogous to the natural behavior of species used as animal models in memory tasks.